Solid Predominant Histology and High Podoplanin Expression in Cancer-Associated Fibroblast Predict Primary Resistance to Osimertinib in EGFR-Mutated Lung Adenocarcinoma - Yuji Uehara, MD; Hiroki Izumi, MD, PhD; Tetsuro Taki, MD, PhD; Tetsuya Sakai, MD, PhD; Hibiki Udagawa, MD, PhD; Eri Sugiyama, MD, PhD; Shigeki Umemura, MD, PhD; Yoshitaka Zenke, MD, PhD; Shingo Matsumoto, MD, PhD; Kiyotaka Yoh, MD, PhD; Shoko Kubota, MD, PhD; Keiju Aokage, MD, PhD; et al. (JTO Clinical and Research Reports)
Introduction: Resistance to EGFR tyrosine kinase inhibitors is influenced by tumor-intrinsic and -extrinsic factors. We investigated the impact of tumor cell histology and tumor microenvironment on the efficacy of osimertinib. Methods: We evaluated surgically resected adenocarcinoma from patients treated with first-line osimertinib at the National Cancer Center Hospital East (2016–2023), evaluating clinicopathologic characteristics, tumor cell histology, podoplanin expression in cancer-associated fibroblasts (CAFs) identified by immunohistochemistry, and outcomes. We also investigated HGF mRNA expression levels, using The Cancer Genome Atlas Program and Singapore Oncology Data Portal cohorts. Results: The study included 93 patients. Solid (n = 19) versus non-solid predominant (n = 74) histology was not associated with worse disease-free survival after surgery (p = 0.12), but was significantly associated with worse progression-free survival (PFS) and overall survival following osimertinib treatment (p = 0.026, p = 0.004). Similarly, high-podoplanin (n = 31) versus low-podoplanin (n = 62) expression in CAFs was not associated with worse disease-free survival after surgery (p = 0.65), but was significantly associated with worse PFS and showed a trend towards worse overall survival following osimertinib treatment (p < 0.001, p = 0.11). In the multivariable analysis, solid predominant histology and high-podoplanin expression in CAFs were independently associated with worse PFS. In the cohorts of The Cancer Genome Atlas Program and Singapore Oncology Data Portal, EGFR-mutated lung adenocarcinoma with solid predominant histology or high-podoplanin expression exhibited significantly higher HGF expression. Conclusions: Solid predominant histology and high-podoplanin expression in CAFs predicted osimertinib resistance, potentially guiding the selection of patients for more intensive treatments beyond osimertinib monotherapy.